Scientific American. – 1865. – Vol. 12, № 25 - б/а (New York. Munn @ Company, 1865)
A weekly journal of practical information in art, science, mechanics, chemistry and manufactures.
Scientific American. Vol. 12, № 1, 3–26. – New York, 1865. – P. 1–14, 31–414.
Keywords: June 17, 1865; Recent American Patents; Patents; Klahr’s Boring and Mortising Machine; Hawkins’s Diving Mask; Recent English Patents; Lochman’s Liquor-saving Funnel; Sayre’s Churn; Minor’s Pocket Lantern; Boynton’s Damper and Ventilator; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of technology and industry; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Agricultural history; Research Subject Categories::NATURAL SCIENCES::Physics; Research Subject Categories::NATURAL SCIENCES::Chemistry; Research Subject Categories::TECHNOLOGY